Pengembangan Media Edutainment Pembelajaran Aritmatika Sosial Berorientasi pada Pemahaman Konsep Matematis dan Self-Directed Learning - La Ode Adin Hasrun Bici; Wahyu Setyaningrum (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study was conducted to develop an edutainment-based learning media product and to assess its feasibility in terms of validity, practicality, and effectiveness with a focus on understanding mathematical concepts and fostering self-directed learning in social arithmetic topics. The research employed a development approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The instruments used included validation sheets completed by experts, practicality questionnaires filled out by teachers and students, mathematical concept comprehension tests, and self-directed learning questionnaires. Research subjects consisted of two groups: a small-scale trial with 10 seventh-grade students and a large-scale trial with 32 students. The findings revealed that the edutainment learning media developed was appropriate for use, fulfilling all three aspects of feasibility. The validity score for media was 142 out of 230 (medium category), while the material validation reached 110 out of 135 (high category). Practicality assessments showed very high results, with teachers assigning a score of 175 out of 172 indicators and students achieving an average score of 156.8, which placed the media in the very high category. Effectiveness was demonstrated by improved mathematical concept comprehension, where the pretest average of 75.24 increased to 84.38 in the posttest, meeting the minimum high category. Similarly, the self-directed learning questionnaire showed improvement, with average scores rising from 99.97 to 102.91, and the percentage of students attaining very high posttest results increased to 90.63%.